2022
DOI: 10.3390/molecules27134090
|View full text |Cite
|
Sign up to set email alerts
|

Mushroom Polysaccharide-Assisted Anticarcinogenic Mycotherapy: Reviewing Its Clinical Trials

Abstract: Of the biologically active components, polysaccharides play a crucial role of high medical and pharmaceutical significance. Mushrooms have existed for a long time, dating back to the time of the Ancient Egypt and continue to be well explored globally and experimented with in research as well as in national and international cuisines. Mushroom polysaccharides have slowly become valuable sources of nutraceuticals which have been able to treat various diseases and disorders in humans. The application of mushroom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 98 publications
0
13
0
Order By: Relevance
“…These bioactive compounds include proteins, fats, polysaccharides, flavonoids, terpenoids, minerals and organic acids [38]. The available literature suggests that mushroom extracts and polysaccharides may have anticancer properties, however, little is known of their mechanisms of action [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…These bioactive compounds include proteins, fats, polysaccharides, flavonoids, terpenoids, minerals and organic acids [38]. The available literature suggests that mushroom extracts and polysaccharides may have anticancer properties, however, little is known of their mechanisms of action [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…The participants fulfilled the following inclusion criteria: (1) at informed consent, male/female subjects aged more than or equal to 20 and less than 65 years; (2) subjects who had a bowel evacuation 3 to 7 times per week; and (3) those who showed understanding of the study procedures and agreed to participate by providing written informed consent prior to the study. Key exclusion criteria were as follows: (1) subjects who had a plan or who had taken medication within a month before the start of trial, which would affect the trial result; (2) subjects who regularly consumed food for specified health uses, food with function claims, supplements and/or health foods more than thrice per week that would affect the trial results; (3) subjects who regularly consumed mushrooms no less than 6 days per week; (4) subjects who had difficulty restricting mushroom intake to less than 2 days per week, as well as less than 50 g a week; (5) subjects who disliked mushrooms; (6) subjects who had undergone an appendectomy; (7) subjects who received surgery that would affect the trial result within half a year before obtaining consent; (8) subjects who had a previous/current medical history of severe cardiac, hepatic, renal or digestive diseases; (9) pregnant, possibly pregnant, or lactating women; (10) subjects who consumed excessive alcohol; (11) subjects with irregular lifestyles and irregular dietary habits; (12) subjects who had food allergies; (13) subjects who were planning to receive a vaccination during the trial; (14) subjects who were enrolled in other clinical tests with some kind of medicine/food, who took part in those within 4 weeks before this trial, or who joined those after giving informed consent to participate in this trial; (15-17) subjects who donated their blood components and/or whole blood, as indicated-all subjects: 200 ml within the last month, males: 400 ml within the last 3 months, and females: 400 ml within the 4 months prior to this trial; (18) males who had 1200 ml in total of their blood collected within the last 12 months, after adding the blood volumes planned to be sampled during this trial; (19) females who had 800 ml in total of their blood collected within the last 12 months, after adding the amounts of blood planned to be sampled during this trial; and (20) others who were determined ineligible by the principal/sub-principal investigator. Randomization in this trial was performed using the blocked stratified randomization method with the subject assignment manager.…”
Section: Clinical Trialmentioning
confidence: 99%
“…According to previous studies, it is possible that the consumption of various types of mushrooms may contribute to host immune system regulation in relation to SCFA levels and IgA production. In addition, it has been reported that the mushroom polysaccharides act directly on immune cells and show anticancer effects ( 19 ). However, there have been no reports of human consumption of various types of mushrooms, especially in terms of their effects on the immunity related to mucosal surfaces homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Coriolus versicolor extract, containing polysaccharide K (PSK) and polysaccharide peptide (PSP), is able to immunomodulate and induce the production of lymphocytes and cytokines, such as interferons and interleukins, exhibiting antioxidant activities ( 74 ) and used in anti-cancer mycotherapy ( 75 ).…”
Section: Bioactive Molecules Of Mushroomsmentioning
confidence: 99%
“…For many years PSP, pleuran, lentinan, grifolan, krestin-PSK, schizophyllan, and scleroglucan have been well-described bioactive polysaccharides from the mushroom origin, used as biopharmaceuticals with widespread clinical significance ( 75 ).…”
Section: Bioactive Molecules Of Mushroomsmentioning
confidence: 99%